(untitled) (Journal of actual problems of jurisprudence, 2019)
In article features of administratively-right protection objects of the state prirodno-reserved fund of Republic Kazakhstan are considered. On the basis of the analysis of the Code of Republic Kazakhstan about administrative offences lacks of the operating administrative legislation are revealed, and also offers on its perfection are formulated.